Genetic study of atypical femoral fractures using exome sequencing in three affected sisters and three unrelated patients - Roca-Ayats, N; Falcó-Mascaró, M; García-Giralt, N; Cozar, M; Abril, JF; Quesada-Gómez, JM; Prieto-Alhambra, D; Nogués, X; Mellibovsky, L; Díez-Pérez, A; Grinberg, D; Balcells, S (Ibáñez and Plaza Asociados S.L, 2018)
Objectives: Atypical femoral fractures (AFF) are rare, often related to long-term bisphosphonate (BPs) treatment. Their pathogenic mechanisms are not precisely known and there is no evidence to identify patients with a high risk of AFF. The aim of this work is to study the genetic bases of AFFs. Material and methods: Whole-exome sequencing was carried out on 3 sisters and 3 unrelated additional patients, all treated with BPs for more than 5 years. Low frequency, potentially pathogenic variants shared by the 3 sisters, were selected, were selected and a network of gene and protein interactions was constructed with the data found. Results: We identified 37 rare variants (in 34 genes) shared by the 3 sisters, some not previously described. The most striking variant was the p.Asp188Tyr mutation in the enzyme geranylgeranyl pyrophos-phate synthase (encoded by the GGPS1 gene), from the mevalonate pathway and essential for osteoclast function. Another noteworthy finding was two mutations (one in the 3 sisters and one in an unrelated patient) in the CYP1A1 gene, involved in the metabolism of steroids. We identified other variants that could also be involved in the susceptibility to AFFs or in the underlying osteoporotic phenotype, such as those present in the SYDE2, NGEF, COG4 and FN1 genes. Conclusions: Our data are compatible with a model where the accumulation of susceptibility variants could participate in the genetic basis of AFFs.